2022
DOI: 10.3390/catal12111417
|View full text |Cite
|
Sign up to set email alerts
|

Co(OH)2 Nanoflowers Decorated α-NiMoO4 Nanowires as a Bifunctional Electrocatalyst for Efficient Overall Water Splitting

Abstract: The development of bifunctional electrocatalysts with high catalytic activity and cyclic stability is an effective method for electrocatalytic water splitting. Herein, a promising hydroxide/oxide Co(OH)2/α-NiMoO4 NWs/CC heterostructure with nanoflowers decorating the nanowires was fabricated on a carbon cloth (CC) substrate via hydrothermal and calcination methods. In contrast to one-dimensional nanomaterials, the interfaces of Co(OH)2 nanoflowers and α-NiMoO4 nanowires on CC provide more active sites for elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Nevertheless, this electrode has the potential for use in various other elds. 179,180 The study performed by He et al 181 is focused on the electrochemical performance of as-fabricated catalysts towards the OER in 0.1 M KOH electrolyte. The catalysts studied include sol-gel-derived SFM, as-spun SFM nanowires (SFM-NF), bare SFM hollow nanobers, and Co(OH) 2 /SFM-NF.…”
Section: Doped-cobalt Hydroxides As Oer Electrocatalystsmentioning
confidence: 99%
“…Nevertheless, this electrode has the potential for use in various other elds. 179,180 The study performed by He et al 181 is focused on the electrochemical performance of as-fabricated catalysts towards the OER in 0.1 M KOH electrolyte. The catalysts studied include sol-gel-derived SFM, as-spun SFM nanowires (SFM-NF), bare SFM hollow nanobers, and Co(OH) 2 /SFM-NF.…”
Section: Doped-cobalt Hydroxides As Oer Electrocatalystsmentioning
confidence: 99%
“…Since the oxidation reaction has occurred and the state of the metal is changed, this changed electronic configuration will now take part in the OER. [56][57][58][59][60][61][62] The overpotential is measured and compared at 100 mA cm À2 . WS 2 @UiO-66(1 : 2) requires an overpotential of around about 550 mV to attain 100 mA cm À2 current density, which is less than bulk WS 2 (650 mV), exfoliated WS 2 (610 mV), WS 2 @UiO-66(1 : 1) (570 mV), and WS 2 @UiO-66(1 : 3) (570 mV).…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%
“…The theoretical calculations and experimental results showed that Ni-O-Fe structures offer exceptional catalytic activity in terms of oxygen electrochemistry [ 128 ]. Xu et al [ 129 ] developed cobalt hydroxide nanoflowers-decorated α-NiMoO 4 nanowires as functional electrocatalysts for water splitting reactions. They decorated the Co(OH) 2 /NiMoO 4 nanowires on a carbon cloth via a simple HT process, which formed as one-dimensional nanoarchitectures, providing a lower overpotential toward the HER of 183 mV and the OER of 170 mV at a current density of 10 mA cm −2 in 1.0 M KOH electrolytes, showing good long-term stability.…”
Section: Solid Supports For Metal Oxhs For Oer and Hermentioning
confidence: 99%